Retinopathy and nephropathy in type 1 diabetic patients : association with polymorphysms of vitamin D-receptor, Tnf, neuro-D and Il-1 receptor 1 genes - Bućan, Kajo (Array, 2009)
Summary: Retinopathy and nephropathy are common late type 1 diabetes mellitus (T1D) complications. In this study we investigated whether individual differences in 4 candidate genes significantly contribute to development and progression of late complications in T1D patients. We examined 121 patients for the presence of diabetic retinopathy and nephropathy. We genotyped variants in vitamin D receptor (VDR) and tumor necrosis factor (TNF) genes in 47 patients and in NeuroD1 and interleukin-1 receptor 1 (IL1R1) genes in 35 patients. Diabetic retinopathy had 66 (55%) patients after a median of 13.0 years after diagnosis. Diabetic nephropathy had 14 (11.66%) patients, all of whom had already developed retinopathy. A significant correlation between the degree of diabetic retinopathy and mean microalbuminuria (MA) value has been found (c2=54.18, p<0.001). After correcting for duration of disease, only the VDR gene BsmI genotypes showed significant association with cumulative prevalence of diabetic retinopathy, while no investigated genetic polymorphysms could reliably predict diabetic nephropathy